Analisis keberadaan pabrik kelapa sawit terhadap kondisi sosial ekonomi masyarakat pendatang yang menetap di Desa Ladang Panjang Kecamatan Sungai Gelam Kabupaten Muaro Jambi - Aldi, Muhammad; Zulgani, Zulgani; Parmadi, Parmadi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2023)
The demand for electrical energy continues to increase along with population growth and technological developments. The household, industrial and commercial sectors are the main sectors for the use of electrical energy. Electricity also plays a crucial role in supporting national defense so that the government continues to strive to meet the electrical energy needs. Aligned with Indonesia's commitment to reduce greenhouse gases to support achieving net-zero emissions, the government promotes the utilization of new renewable energy, one of which is geothermal energy. Indonesia is known to have the largest geothermal energy potential in the world. Geothermal power plants are environmentally friendly, the life cycle of the plant is associated with environmental impacts and typically requires substantial initial investment. The research methodology used in this article is a literature review to analyze the environmental impact and life cycle cost of geothermal power plants. The results show that the operational activities are the primary source of environmental impacts. GPP produces low emissions and are economically competitive when compared to solar photovoltaic (PV) energy.